Analysis of The Knowledge and Understanding Level of Madrasah Tsanawiyah Science Teachers in Banda Aceh in Constructing Exam Questions - Yusrizal, Y.; Rahmati, R. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2021)
This study aims to (1) determine the level of knowledge and understanding of Madrasah Tsanawiyah (MTsN) science teachers in constructing exam questions, (2) describe the knowledge and understanding of MTsN science teachers in writing questions based on the cognitive level of Bloom's taxonomy. This research is descriptive quantitative type. The data collection was carried out by a survey method using a developed questionnaire instrument. The population in this study were all MTsN (Islamic Junior High School) science teachers in Banda Aceh. The data obtained were analyzed descriptively. The results showed that: (1) most of the MTsN Banda Aceh science teachers already have very high knowledge and high understanding in constructing exam questions. (2) Knowledge and understanding of constructing questions are limited to levels C1, C2, C3 and C4. For questions on cognitive levels C5 and C6, some MTsN science teachers do not know and understand how to construct them. This research can be information for various parties who hold training or question writing workshops so that they can provide material that is right on target or is still not mastered by the teacher.